What Controls Direct Hole-Mediated Oxidation Kinetics in a Carbon Nitride-Based Photocatalytic System: A Model Study for Aqueous Aromatic Compounds - Hu, Yi; Du, Juanshan; Moon, Gun-hee; Choi, Wonyong (American Chemical Society, 2023)
Polymeric carbon nitride (CN)-based materials enable the visiblelight-induced photocatalytic oxidation (PCO) mainly through the reductive pathway (O-2. H2O2. center dot OH) to generate reactive oxygen species (ROS) because the CN valence band edge position is not sufficiently positive to oxidize water directly to generate center dot OH. Consequently, the hole-mediated process in the CN-PCO system has been largely overlooked. In this study, we conducted a comprehensive investigation of the PCO behavior of pristine and modified CN materials to assess the role of direct hole transfer in oxidizing aromatic compounds as a model substrate. The direct hole-mediated oxidation path was investigated in the anoxic aqueous suspension containing Cu2+ or BrO3- as an alternative electron acceptor while inhibiting the ROS formation via the O-2 reduction pathway. The observed rate constant exhibited a logarithmic correlation with both the Hammett constant (s) and the half-wave-oxidation potential (E1/2) for 12 phenols and 6 anilines. The analysis using (i) Fukui function, (ii) the energy of the highest occupied molecular orbital (HOMO), and (iii) the acid dissociation constant (pKa) provided insights into the role of the hydroxyl and amine substituents as a reactive site for the hole transfer reaction. These findings propose that the hole-driven extraction of an electron from substituted aromatic compounds is a rate-determining step in the overall PCO process. The study identified the key descriptors that exhibit pronounced correlation with the PCO kinetics, which should be useful in understanding and developing the CN-based photocatalytic systems.